2017
DOI: 10.1007/s13361-016-1577-8
|View full text |Cite
|
Sign up to set email alerts
|

Five Micron High Resolution MALDI Mass Spectrometry Imaging with Simple, Interchangeable, Multi-Resolution Optical System

Abstract: High-spatial resolution mass spectrometry imaging (MSI) is crucial for the mapping of chemical distributions at the cellular and subcellular level. In this work, we improved our previous laser optical system for matrix-assisted laser desorption ionization (MALDI)-MSI, from ~9 μm practical laser spot size to a practical laser spot size of ~4 μm, thereby allowing for 5 μm resolution imaging without oversampling. This is accomplished through a combination of spatial filtering, beam expansion, and reduction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 38 publications
1
83
0
Order By: Relevance
“…Most recently our group has further modified our optics setup to achieve a practical laser spot size of~4 mm which enabled 4-5 mm spatial resolution imaging to be accomplished without the need for oversampling. [16] In the previous work, a home-built Keplerian optical configuration was used as a beam expander, but this work uses a commercially available Galilean configuration beam expander to simplify the optics. In addition, a 1 mm pinhole was utilized instead of the 25 mm pinhole due to the difficulties in optical alignment with such a small pinhole, although the larger pinhole does not remove all the non-Gaussian beam components.…”
Section: Simple Interchangeable Multi-resolution Optical System Witmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently our group has further modified our optics setup to achieve a practical laser spot size of~4 mm which enabled 4-5 mm spatial resolution imaging to be accomplished without the need for oversampling. [16] In the previous work, a home-built Keplerian optical configuration was used as a beam expander, but this work uses a commercially available Galilean configuration beam expander to simplify the optics. In addition, a 1 mm pinhole was utilized instead of the 25 mm pinhole due to the difficulties in optical alignment with such a small pinhole, although the larger pinhole does not remove all the non-Gaussian beam components.…”
Section: Simple Interchangeable Multi-resolution Optical System Witmentioning
confidence: 99%
“…One is the ability to identify unknown compounds directly on tissues without chromatographic separation, and the other is the limited sensitivity in small sampling sizes. We have developed a 'multiplex MS imaging' technique to address the former issue, [14][15][16] and developed various new matrices to address the latter. [17,18] We have divided this review into three major subjects describing our efforts: 1) to achieve small laser spot sizes, 2) to develop multiplex MS imaging, and 3) to expand the variety of currently available matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of pixel size in MALDI-MSI is the area of desorption/ionisation on the tissue surface, that, in turn, is dependent on the laser spot size. Several groups have reported optical modifications to commercial MALDI-MSI ion sources that have reduced the laser spot size and, thus, achievable pixel sizes, down to < 10 μm and at best~1 μm [11][12][13][14][15]. For example, Kompauer et al recently reported a modified atmospheric pressure MALDI-MSI source capable of reaching 1.4 μm pixel size and imaging lipids within single cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…MSI is becoming a powerful analytical tool in biomedical and life sciences . The instrument technologies of MALDI mass spectrometers have greatly advanced in the past decade: for instance, implementing high‐repetition solid‐state lasers, continuous raster sampling, and galvanometer‐based optical scanners for improved throughput; spatially structured laser beam profiles and laser‐induced post‐ionization for improved sensitivity; laser beam shaping, fiber‐optic laser delivery systems, and transmission geometry vacuum MALDI source for improved spatial resolution; stigmatic imaging (microscope mode) instrumentation for both throughput and spatial resolution; and most recently, high‐performance elevated/atmospheric pressure MALDI . It could be argued that MALDI‐MSI applications have led this progress.…”
Section: Introductionmentioning
confidence: 99%